Fight INflammation to Improve outcome after aneurysmal Subarachnoid HEmorRhage (FINISHER) trial: Study protocol for a randomized controlled trial. Issue 2 (February 2023) - Güresir, Erdem; Lampmann, Tim; Bele, Sylvia; Czabanka, Marcus; Czorlich, Patrick; Gempt, Jens; Goldbrunner, Roland; Hurth, Helene; Hermann, Elvis; Jabbarli, Ramazan; Krauthausen, Marius; König, Ralph; et al.
Rationale: Aneurysmal subarachnoid hemorrhage (SAH) has high morbidity and mortality. While the primary injury results from the initial bleeding cannot currently be influenced, secondary injury through vasospasm and delayed cerebral ischemia worsens outcome and might be a target for interventions to improve outcome. To date, beside the aneurysm treatment to prevent re-bleeding and the administration of oral nimodipine, there is no therapy available, so novel treatment concepts are needed. Evidence suggests that inflammation contributes to delayed cerebral ischemia and poor outcome in SAH. Some studies suggest a beneficial effect of anti-inflammatory glucocorticoids, but there are no data from randomized controlled trials examining the efficacy of glucocorticoids. Therefore, current guidelines do not recommend the use of glucocorticoids in SAH. Aim: The Fight INflammation to Improve outcome after aneurysmal Subarachnoid HEmorRhage (FINISHER) trial aims to determine whether dexamethasone improves outcome in a clinically relevant endpoint in SAH patients. Methods and design: FINISHER is a multicenter, prospective, randomized, double-blinded, placebo-controlled clinical phase III trial which is testing the outcome and safety of anti-inflammatory treatment with dexamethasone in SAH patients. Sample size estimates: In all, 334 patients will be randomized to either dexamethasone or placebo within 48 h after SAH. The dexamethasone dose is 8 mg tds for days 1–7 and then 8 mg od for days 8–21. Study outcome: The primary outcome is the modified Rankin Scale (mRS) at 6 months, which is dichotomized to favorable (mRS 0–3) versus unfavorable (mRS 4–6). Discussion: The results of this study will provide the first phase III evidence as to whether dexamethasone improves outcome in SAH.